2011
DOI: 10.1016/j.jbi.2011.02.009
|View full text |Cite
|
Sign up to set email alerts
|

Incremental Gaussian Discriminant Analysis based on Graybill and Deal weighted combination of estimators for brain tumour diagnosis

Abstract: In the last decade, machine learning (ML) techniques have been used for developing classifiers for automatic brain tumour diagnosis. However, the development of these ML models rely on a unique training set and learning stops once this set has been processed. Training these classifiers requires a representative amount of data, but the gathering, preprocess, and validation of samples is expensive and time-consuming. Therefore, for a classical, non-incremental approach to ML, it is necessary to wait long enough … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0
1

Year Published

2014
2014
2015
2015

Publication Types

Select...
3
3
2

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 37 publications
0
20
0
1
Order By: Relevance
“…In such cases, the implementation of incremental learning algorithms is a promising solution for clinical environments. Tortajada et al [53] evaluated the performance of an incremental classifier based on single voxel Short TE spectra in comparison to static classifiers. The results revealed that the classification performance was improved when the incremental classifiers were used comparing to performance of the static classifies.…”
Section: Future Perspectivesmentioning
confidence: 99%
“…In such cases, the implementation of incremental learning algorithms is a promising solution for clinical environments. Tortajada et al [53] evaluated the performance of an incremental classifier based on single voxel Short TE spectra in comparison to static classifiers. The results revealed that the classification performance was improved when the incremental classifiers were used comparing to performance of the static classifies.…”
Section: Future Perspectivesmentioning
confidence: 99%
“…This is highly convenient since there exists large 1.5T databases compiled throughout several years and the prediction models based on 1.5T acquisitions can be used for diagnosis of cases acquired with 3T instruments. In addition, the result reported in [125] can also be applied to the work presented by Tortajada et al [126], where they presented an incremental learning algorithm and successfully applied it to several diagnosis classification problems using MR spectra. Tortajada et al realized that in a clinical or research setting, the gathering, pre-process, and validation of samples is expensive and time-consuming.…”
Section: Survey Of Studies Performed With Mrs Data From Adultsmentioning
confidence: 88%
“…Unlike many of the state-of-the-art incremental learning algorithms, we assume that, once the datasets are used for fitting the models, they will not be available again. The first incremental learning algorithm is based on maximum-likelihood parameter estimation and a weighted combination of the old model parameters with the new dataset to develop a new model [28]. The second incremental learning algorithm is based on the Bayesian inference paradigm.…”
Section: Contributionsmentioning
confidence: 99%
“…However, there are real scenarios with data protection policies or possible conflict of interests where the previous data are not available if a model trained with data from one organization is moved to another organization. For instance, when a model is moved from one hospital to another, patient consent and ethical approval needs to be obtained to send and store data [28]. In order to take into account this condition, we will assume that previous data are not accessible at all.…”
Section: Incremental Learningmentioning
confidence: 99%
See 1 more Smart Citation